Ergonomic risk assessment of musculoskeletal disorders (MSD) during simulated endotracheal intubation in Hospital Universiti Sains Malaysia (HUSM) - Noor, Mohamad Hamzi Mohamad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2020)
Background: Endotracheal intubation is a form of airway procedure usually performed in the emergency department. This procedure is done as a method to secure the airways of patients during cardiac arrest. Body posture during intubation may cause musculoskeletal problems, but doctors usually do not have the awareness on the ergonomic factors and the effects on their health. There is a rise in the prevalence of work-related musculoskeletal disorder (MSD) in medical personnel performing this procedure due to lack of ergonomic postures. There is little evidence on the optimum bed level for intubation in association with ergonomic body posture during tracheal intubation. Objectives: This study was performed to evaluate the effects of different bed levels during endotracheal intubation on ergonomic body postures, intubation time and success rates of procedures and to find the optimum bed level for intubation with lower risk of MSD, shortest time and higher success rate. Method: This cross-sectional study was performed among 80 master’s students using the rapid entire body assessment (REBA) method. This study was carried out at the resuscitation zone of the accident and emergency department in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. During this study, 80 doctors were asked to perform endotracheal intubation using a mannequin at three different bed levels: supra pubic, umbilical and sub-xyphoid levels. At each level, their body posture, intubation time and success rate were recorded. We compared the mean of REBA score, mean of time and success rate for each level Result: This study showed that there were significantly lower risks for MSD and shorter intubation time when the procedure was performed at the sub-xyphoid level. However, no significant differences in performance were observed. Conclusion: Medical personnel should be advised to intubate patients at the sub-xyphoid level. The finding of the study can be used for teaching and learning purposes.